ANALISIS BIAYA DAN PENERIMAAN USAHATANI TOMAT DI DESA WAKULI KECAMATAN KAPONTORI KABUPATEN BUTON - Suriadi, Suriadi (Media Agribisnis, 2017)
Abstract   Problem statements in this research are: how much is the cost incurred by farmers in tomato farming in Waklii Village, Kapontori Sub-district, Buton Regency and how much is the income obtained from tomato farming in Wakuli Village, Kapontori Sub-district, Buton Regency. This study aims to determine how much the average cost received by farmers from tomato farming in Wakuli Village, Kapontori Sub-district Buton Regency and how much the average income received by tomato farmers in Wakuli Village, Kapontori sub-district, Buton Regency, this research was carried out in Wakuli Village, Kapontori Sub-district of Buton Regency for two months from June to July 2015. The population of this study was existing tomato farmers, the research sample took 30 tomato farmers. Data were collected through interviews using questionnaires and data analysis using cost and revenue analysis. The results showed that the costs incurred by farmers in conducting tomato farming activities with an average land area of 1 ha with an average cost of IDR 5,715,983 and the average acceptance of IDR 14,303,667, with the average income of the respondent farmers, is IDR 8,587,983. Recommendations Local governments, especially at the regency level, need to establish regulations relating to the tomato marketing system, especially determining basic prices.   Keywords: cost and acceptance analysis, tomato farming